Youth, TikTok, and #FreePalestine: New Media and Political Consciousness in Indonesia (Palestine Issues on Indonesian Society, 2025)
This study explores the role of TikTok and other new media platforms in shaping political consciousness about Palestine among Indonesian youth. Focusing on the hashtag #FreePalestine, this paper investigates how Indonesian TikTok users engage with global political movements, focusing on the ways in which short-form video content is used to mobilize, educate, and advocate for Palestinian rights. Through an analysis of TikTok videos, trends, and user engagement, this paper assesses the efficacy of TikTok in raising awareness of Palestinian struggles, fostering a sense of solidarity, and prompting political action. The study highlights the way in which TikTok serves as an alternative space for political discourse outside traditional media outlets, allowing youth to express opinions, spread messages of activism, and critique national and international policies. By focusing on the interactions between Indonesian youth and the #FreePalestine campaign, the paper sheds light on how social media and digital activism intersect with generational shifts in political engagement. This paper ultimately explores how new media platforms like TikTok are reshaping political activism and solidarity movements in Indonesia.